2017
DOI: 10.14744/anatoljcardiol.2017.7730
|View full text |Cite
|
Sign up to set email alerts
|

“Desert” gene (Chr9p21) variants as novel markers for coronary artery disease

Abstract: Objective:Previous reports have denoted to the possible link of Chr9p21 locus to the incidence of coronary artery disease (CAD). The entire core of chr9p21 is covered by “ANRIL” (Antisense noncoding RNA in INK4 Locus) and lies in a region that is free from any coding proteins; therefore, it is called the desert gene. The major objectives of this study were to examine the association of rs10757278 and rs2383206 SNPs on Chr9p21 with the incidence of CAD in the presence and absence of type 2 diabetes (T2D) in Egy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…Nevertheless, downregulation of ANRIL in CAD patients was also documented in other studies [49][50][51]. This discrepancy could be attributed to different Chr9p21 locus genotypes as the Chr9p21 rs10757278/rs2383206-G risk allele associated with increased ANRIL expression is prevalent in Egyptian CAD patients [52,53]. In fact, and to our knowledge, this study addressed for the first time the upregulated expression level of CDK4 and E-cadherin in CAD patients.…”
Section: Discussionsupporting
confidence: 47%
“…Nevertheless, downregulation of ANRIL in CAD patients was also documented in other studies [49][50][51]. This discrepancy could be attributed to different Chr9p21 locus genotypes as the Chr9p21 rs10757278/rs2383206-G risk allele associated with increased ANRIL expression is prevalent in Egyptian CAD patients [52,53]. In fact, and to our knowledge, this study addressed for the first time the upregulated expression level of CDK4 and E-cadherin in CAD patients.…”
Section: Discussionsupporting
confidence: 47%
“…Samaneh et al demonstrated in a cohort study, which enrolled 420 patients with CHD from the population of the Tehran lipid and glucose study (TLGS) and matched 407 healthy controls with age and sex, that the presence of risk alleles of an ANRIL SNP (rs7865618) was associated with CHD ( P = .03; OR: 1.73; CI 95%: 1.04‐2.88) . Heba et al conducted a case‐control study consisting of 50 healthy individuals and 100 patients and found that the rs10757278 (OR: 1.92, P = .0002) and rs2383206 (OR: 1.729, P = .0004) SNPs in ANRIL ( P < .001) increased the risk for CAD . In a case‐control study including 33 T2DM patients with CHD and 31 T2DM patients alone, Esmaeil et al found that the expression of ANRIL was associated with CHD in diabetic patients, and ANRIL was upregulated (2.34‐fold, P = .012) in T2DM with CHD.…”
Section: Resultsmentioning
confidence: 99%